Trim the fat: the role of omega-3 fatty acids in psychopharmacology - Madeeha Nasir; Michael H. Bloch (SAGE Publishing, 2019)
The American Psychiatric Association (APA) currently recommends the use of omega-3 fatty acid supplementation for depressive disorders, impulse-control disorders, and psychotic disorders in treatment guidelines. This review examines the evidence for efficacy of omega-3 fatty acids in depressive disorders, bipolar disorder, anxiety disorders, post-traumatic stress disorder (PTSD), and psychosis. Meta-analysis of randomized-controlled trials of omega-3 fatty acids for depression are inconclusive, with strong evidence of publication bias, sizable heterogeneity between included studies, and substantial methodological shortcomings in included trials. The large amount of heterogeneity in findings of RCTs of omega-3 fatty acids for unipolar depression is likely attributable to highly heterogeneous sample populations that are given different omega-3 supplements [which differ widely in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) content, ratio, and dosage] as either adjunctive or monotherapy of other existing treatments, and then measure several different outcomes of depression symptomatology with likely incomplete blinding. Evidence of efficacy of omega-3 supplementation in treating psychosis, PTSD, anxiety, and bipolar mania is minimal. The current guidelines recommending the use of omega-3 fatty acids in adulthood psychiatric conditions should be revisited, especially given several recent negative studies examining the effects of omega-3 fatty acids for cardiovascular disease. Recommending likely ineffective treatment to patients, no matter how benign the side-effect profile, has opportunity cost (e.g. other more effective medications or therapies not being utilized) and likely affects patient compliance with other evidence-based treatments.